The real-life experience with cardiovascular complications in the first dose of fingolimod for multiple sclerosis - Fragoso, Yara Dadalti (2014)
Fingolimod is a new and efficient treatment for multiple sclerosis (MS). The drug administration requires special attention to the first dose, since cardiovascular adverse events can be observed during the initial six hours of fingolimod ingestion. The present study consisted of a review of cardiovascular data on 180 patients with MS receiving the first dose of fingolimod. The rate of bradycardia in these patients was higher than that observed in clinical trials with very strict inclusion criteria for patients. There were less than 10% of cases requiring special attention, but no fatal cases. All but one patient continued the treatment after this initial dose. This is the first report on real-life administration of fingolimod to Brazilian patients with MS, and one of the few studies with these characteristics in the world.